Alcoholic Fermentation Enhances in Vitro and Cellular Antioxidant Capacity and in Vitro Antihypertensive Potential of Native Chilean Fruits Algarrobo (Neltuma Chilensis) and Chañar (Geoffroea Decorticans) - Cubillos-Riffo, F; Echeverria-Morgado, J; Mitsi, C (Elsevier Ltd, 2025)
The present study aimed to investigate the effect of alcoholic fermentation with Saccharomyces cerevisiae on the chemical composition, antioxidant capacity, and antihypertensive potential of extracts from two Chilean native pulses: algarrobo (Neltuma chilensis (Molina) C.E.Hughes & G.P.Lewis) and chañar (Geoffroea decorticans (Gill. ex Hook. et Arn.). The fermentation process increased the Total Phenolic and Total Flavonoid Content in both algarrobo and chañar extracts. Fermented extracts (FEs) showed higher concentrations of organic acids, a decrease in glucose and fructose levels, and glycerol. LC-MS analysis revealed a greater diversity of compounds in FEs, including various chemical superclasses not detected in aqueous extracts (AEs). Fermentation significantly enhanced the in vitro and cellular antioxidant capacity of both fruits. FEs and non-fermented extracts (AEs) exhibited in vitro antihypertensive potential, associated with the in vitro inhibition of the Angiotensin Converting Enzyme I (ACE I) and renin, with FEs generally showing enhanced bioactivity. Our findings suggest that alcoholic fermentation enhances the antioxidant and antihypertensive properties of algarrobo and chañar, verifying its potential to enhance the nutritional and medicinal value of these native Chilean fruits. © 2025 Elsevier Ltd